Alkyltin Keggin Clusters Templated by Sodium. (14th June 2017) - Saha, Sumit; Park, Deok‐Hie; Hutchison, Danielle C.; Olsen, Morgan R.; Zakharov, Lev N.; Marsh, David; Goberna‐Ferrón, Sara; Frederick, Ryan T.; Diulus, J. Trey; Kenane, Nizan; Herman, Gregory S.; Johnson, Darren W.; et al.
Abstract: Dodecameric (Sn12 ) and hexameric topologies dominate monoalkyltin–oxo cluster chemistry. Their condensation, triggered by radiation exposure, recently produced unprecedented patterning performance in EUV lithography. A new cluster topology was crystallized from industrial n ‐BuSnOOH, and additional characterization techniques indicate other clusters are present. Single‐crystal X‐ray analysis reveals a β‐Keggin cluster, which is known but less common than other Keggin isomers in polyoxometalate and polyoxocation chemistry. The structure is formulated [NaO4 (BuSn)12 (OH)3 (O)9 (OCH3 )12 (Sn(H2 O)2 )] (β‐NaSn13 ). SAXS, NMR, and ESI MS differentiate β‐NaSn13, Sn12, and other clusters present in crude " n ‐BuSnOOH" and highlight the role of Na as a template for alkyltin Keggin clusters. Unlike other alkyltin clusters that are cationic, β‐NaSn13 is neutral. Consequently, it stands as a unique model system, absent of counterions, to study the transformation of clusters to films and nanopatterns.